Colloid Cyst Detection through MRI and CT Scan Images - Bhattacharyya, Debnath; Thirupathi Rao, N.; Kim, Tai-hoon (International Journal of Engineering and Technology, 2019)
A Colloid Cyst is a tumor which has gelatinous material in the human brain. Basically it starts and mostly exists in the anterior parts of the   third ventricle of human brain. The occurrence or the presence these tumors or the cysts can reduce the flow of blood to the major parts of the brain. As a result of this, the functioning of the brain affected at various parts as result the intracranial pressure, blood pressure of the patient’s increases. This sudden increase of pressure might cause the death of the patients too. In the present paper, a new algorithm has been proposed to work with Mean filter to reduce the Noise on the image borders and can be achieved by the usage of Sobel Edge Detector. The working of the present model in three phases and those phases are pre-processing, segmentation and feature extraction. The results of the method show some improvement in the accuracy of identification of cysts in comparison with the existing model of median filters with Gaussian Blur models.